1999
DOI: 10.1111/j.1469-8749.1999.tb00522.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐ or low‐technology measurements of energy expenditure in clinical gait analysis?

Abstract: The repeatability of energy-expenditure measurements were studied in five children and four adults without disabilities using the Cosmed K4 (high technology). The ability to detect change in measurements was compared between this instrument and the Physiological Cost Index (PCI; low technology). The results of repeatability (95% range) for oxygen cost were 13.1% in children and 13% in adults. In contrast, the SD of PCI was 6 to 72% of the mean in adults and wider in children (91%; 95% range). The validity of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
41
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 16 publications
(18 reference statements)
0
41
1
Order By: Relevance
“…However, it is uncomfortable for patients and involves sophisticated and expensive equipment, requiring restricted and specialized handling. 5 Other methods used to estimate energy expenditure are based on cardiac activity. 6 Heart rate (HR) and oxygen uptake are linearly correlated during aerobic exercise.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is uncomfortable for patients and involves sophisticated and expensive equipment, requiring restricted and specialized handling. 5 Other methods used to estimate energy expenditure are based on cardiac activity. 6 Heart rate (HR) and oxygen uptake are linearly correlated during aerobic exercise.…”
Section: Introductionmentioning
confidence: 99%
“…However, the reliability of the Physiologic CostIndex as a measuring tool when dealing with treatment outcomes in patients with cerebral palsy is in doubt. Recent investigations have shown that it is somewhat unreliable when compared to other metabolic measurements [9] .Energy Expenditure Index heart rate expressed per distance walked provides information on energy economyas oxygen uptake perdistancewalked does.Therefore the heart rate by the distance walked provides an easily, reliable measure and assessment of the degree of walking impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Wheelchair ergometers, roller systems, and arm crank tests are convenient methods for laboratory testing but may not accurately assess daily wheelchair propulsion. The optimal test of functioning incorporates the individual's usual aids and orthoses at his or her self-selected speed instead of an imposed speed on a treadmill or ergometer [20].…”
Section: Introductionmentioning
confidence: 99%